Comparison of routing protocols for underwater sensor networks: a survey. (1st January 2011) - Giantsis, Chris; Economides, Anastasios A.
Sensor networks in underwater environments face unique adverse conditions. In order to be functional, specialised routing protocols are required to route the data from source to destination. This paper surveys routing protocols for underwater sensor networks. The routing protocols are examined and compared with respect to the network conditions and quality measures such as packet delivery ratio, average packet delay, energy consumption among others. Advantages and disadvantages of each routing protocol are pointed out.